An Analysis Liquidity Ratio in Performance Assessing Company Financial at Bank Sumut KCP Syariah 2018-2020 - Nia Wariska Harahap; Rahima Purba; Junawan (Britain International for Academic Research (BIAR-Publisher), 2022)
PT Bank Sumut Syariah was established after the issuance of Law No. 10 of 1998 which provided an opportunity for conventional banks to establish a Sharia Business Unit. Based on this and the commitment of the Bank of North Sumatra to the development of sharia services, on November 4, 2004, Bank of North Sumatra opened a Sharia Business unit which is a work unit of the conventional Bank of North Sumatra that functions as an office that carries out business activities based on sharia principles, or a work unit of a branch. from a bank domiciled abroad that functions as the main office of the sharia sub-branch office and or sharia business unit. Bank Sumut Syariah is one of the banks that operate based on sharia principles by BI principle license No. 62 DPIPPrzMdn April 28, 2004.